Perioperative treatment of hemophilia A patients: blood group O patients are at risk of bleeding complications. (19th February 2016) - Hazendonk, H. C. A. M.; Lock, J.; Mathôt, R. A. A.; Meijer, K.; Peters, M.; Laros‐van Gorkom, B. A. P.; van der Meer, F. J. M.; Driessens, M. H. E.; Leebeek, F. W. G.; Fijnvandraat, K.; Cnossen, M. H.
Abstract : Essentials Targeting of factor VIII values is a challenge during perioperative replacement therapy in hemophilia. This study aims to identify the extent and predictors of factor VIII underdosing and overdosing. Blood group O predicts underdosing and is associated with perioperative bleeding. To increase quality of care and cost‐effectiveness of treatment, refining of dosing is obligatory. Summary: Background: Perioperative administration of factor VIII (FVIII) concentrate in hemophilia A may result in both underdosing and overdosing, leading to respectively a risk of bleeding complications and unnecessary costs. Objectives: This retrospective observational study aims to identify the extent and predictors of underdosing and overdosing in perioperative hemophilia A patients (FVIII levels < 0.05 IU mL −1 ). Patients and Methods: One hundred nineteen patients undergoing 198 elective, minor, or major surgical procedures were included (median age 40 years, median body weight 75 kg). Perioperative management was evaluated by quantification of perioperative infusion of FVIII concentrate and achieved FVIII levels. Predictors of underdosing and (excessive) overdosing were analyzed by logistic regression analysis. Excessive overdosing was defined as upper target level plus ≥ 0.20 IU mL −1 . Results: Depending on postoperative day, 7–45% of achieved FVIII levels were under and 33–75% were above predefined target ranges as stated by national guidelines. A potential reduction of FVIII consumption of 44% would have been attained if FVIII levels had been maintained within target ranges. Blood group O and major surgery were predictive of underdosing (odds ratio [OR] 6.3, 95% confidence interval [CI] 2.7–14.9; OR 3.3, 95% CI 1.4–7.9). Blood group O patients had more bleeding complications in comparison to patients with blood group non‐O (OR 2.02, 95% CI 1.00–4.09). Patients with blood group non‐O were at higher risk of overdosing (OR 1.5, 95% CI 1.1–1.9). Additionally, patients treated with bolus infusions were at higher risk of excessive overdosing (OR 1.8, 95% CI 1.3–2.4). Conclusion: Quality of care and cost‐effectiveness can be improved by refining of dosing strategies based on individual patient characteristics such as blood group and mode of infusion.